Effects of dairy and supplemental calcium on food intakes in a group of Jordanian females - Amr, Rula; Elmasri, Khader; Qatatsheh, Ala A.; Mayyas, Amal; Hamad, Islam (Progress in Nutrition, 2018)
Objective. The effect of calcium intervention equivalent to three cups of milk/ day from dairy foods and 800 mg supplemental calcium as tablets, compared to a control group on normal diets with one cup of milk/ day, was studied on food and nutrient intakes. Methods. A group of 122 healthy adult Jordanian females, age 20-45 years, were recruited in the study during a period of 12 weeks.  Study sample was divided into: dairy calcium group, supplemental calcium group, and control group. Intakes of main food groups, energy, carbohydrates, protein, fat, cholesterol, dietary fiber, calcium and vitamin D were evaluated, and their intake adequacies were assessed using the dietary reference intakes (DRIs) and food exchange system at the end of the study. Results. highly significant differences (P0.05) were obtained between the different treatment groups regarding their intakes of fruits and vegetables. As for energy intakes, the control group exhibited a significantly (p